PENGARUH FASILITAS BELAJAR, MOTIVASI BELAJAR, DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN HUMAS KELAS XI OTKP DI SMKN JAKARTA BARAT - Poni Lestari; Corry Yohana; Maulana Amirul Adha (Universitas 17 Agustus 1945 Semarang, Indonesia, 2023)
The purpose of this study was to determine the influence of learning facilities, learning motivation, and learning discipline on the learning outcomes of class XI OTKP public relations subjects of SMK Negeri in West Jakarta. The population in this study is SMKN which has an OTKP major in West Jakarta. The sample in this study was 133 students, this number was obtained from calculations based on the tables of Isaac and Michael. The sampling technique uses the propotional random sampling method. The data collection in this study is secondary data using a questionnaire based on a likert scale for independent variables while for dependent variables using secondary data obtained from the school that is used as the research site in the form of the results of the odd midterm assessment value 2021/2022. The test results using SMARTPLS show: (1) there is an influence between learning facilities on learning outcomes, (2) there is an influence between learning motivation on learning outcomes, (3) there is an influence between learning disciplines on learning outcomes.